Analisis Gagal Antar Surat dan Paket PT Pos Indonesia (Persero) Cabang Sekejati Bandung Menggunakan Metode Fault Tree Analysis (FTA) dan Failure Mode and Effect Analysis (FMEA) - M. Ardhya Bisma; Febriani Sulistiyaningsih; Rivan Alfianto (Masyarakat Ekonomi Syariah Bogor, 2024)
PT Pos Indonesia (Persero) is a State-Owned Enterprise (BUMN) which is active in postal and logistics services. The Postal Processing Center itself is a postal institution whose mission is to plan, organize, implement and control and is responsible for the implementation of the CPTDR process.The occurrence of delivery failures at PT Pos Indonesia (Persero) Sekejati Bandung Branch reached 4% in a period of four months, this shows that DC Sekejati Bandung has not achieved the target determined by the company, where the company itself determines the maximum percentage for delivery failures of only 2%. In the research carried out by the author, the methods used were the Fault Tree Analysis (FTA) Method and also the Failure Mode and Effect Analysis (FMEA) Method to solve the problems that occurred. Based on the results of the analysis carried out, the author found that the most frequent problems were unclear addresses and recipients changing addresses.